2014
DOI: 10.1007/s00455-014-9555-4
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia and Associated Risk Factors Following Extubation in Cardiovascular Surgical Patients

Abstract: Following cardiovascular (CV) surgery, prolonged mechanical ventilation of >48 h increases dysphagia frequency over tenfold: 51 % compared to 3-4 % across all durations. Our primary objective was to identify dysphagia frequency following CV surgery with respect to intubation duration. Our secondary objective was to explore characteristics associated with dysphagia across the entire sample. Using a retrospective design, we stratified all consecutive patients who underwent CV surgery in 2009 at our institution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
3
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 20 publications
(40 reference statements)
6
103
3
10
Order By: Relevance
“…The study sample ranged from 254 (18) to 1042 (10) individuals (mean 781.2). Age varied from 65.4±12.1 (18) to 74.3±8.7 (11) years between the groups of patients with dysphagia and from 62.8±11.8 (10) to 63±0.4 (17) years between the groups of patients without dysphasia. The study by Rousou et al (9) did not consider age as a factor for the development of dysphagia between the groups of individuals undergoing TEE.…”
Section: Characterization Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The study sample ranged from 254 (18) to 1042 (10) individuals (mean 781.2). Age varied from 65.4±12.1 (18) to 74.3±8.7 (11) years between the groups of patients with dysphagia and from 62.8±11.8 (10) to 63±0.4 (17) years between the groups of patients without dysphasia. The study by Rousou et al (9) did not consider age as a factor for the development of dysphagia between the groups of individuals undergoing TEE.…”
Section: Characterization Of Studiesmentioning
confidence: 99%
“…Only studies published in English conducted in the United States (60%) (9,10,17) and Canada (40%) (11,18) were included in this literature review. The study sample ranged from 254 (18) to 1042 (10) individuals (mean 781.2).…”
Section: Characterization Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies that investigate the relationship between TI and changes in swallowing in pediatrics, there is a predominance of the publication of researches performed with adults in which a high prevalence of dysphagia is observed, with 44% to 85%, highlighting multifactor causes that include: oropharyngeal muscle inactivity, glottis lesions, mucosal inflammation and vocal fold ulcerations, as well as mechanical and sensory alterations (25)(26)(27) . A systematic review has shown that prolonged TI may be an independent predictor of dysphagia, and its use increases the risk of upper airway and larynx lesions, which in turn affect the mechanics, aerodynamics, and reflex protection of the upper airways (27) .…”
Section: Figure 2 Distribution Of Classification Of Degree Of Pediatmentioning
confidence: 99%
“…There is no established consensus in the literature regarding the definition of prolonged TI. Its description varies as: greater than 24 hours, greater than 48 hours or up to eight days (25) , being commonly considered as a period greater than 48 hours for the adult population. The present study identified that the presence of dysphagia is associated with a TI time greater than 24 hours, since, from this period, the presence of the orotracheal tube may alter the mechanics and chemoreceptors of the pharyngeal and laryngeal mucosa, causing a change in swallowing reflex and disorder to laryngeal function, which has an impact on the protection mechanisms of the lower airways (23) .…”
Section: Figure 2 Distribution Of Classification Of Degree Of Pediatmentioning
confidence: 99%